Plasmodium falciparum-infected rrythrocyte knob density Is linked to the PfEMP1 variant expressed - Subramani, Ramesh; Quadt, Katharina; Jeppesen, Anine E.; Hempel, Casper; Petersen, Jens Emil Vang; Hassenkam, Tue; Hviid, Lars; Barfod, Lea (mBio, 2015)
Members of the clonally variant Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) family mediate adhesion of infected erythrocytes (IEs) to vascular receptors. PfEMP1 expression is normally confined to nanoscale knob protrusions on the IE surface membrane. To investigate the relationship between the densities of these IE surface knobs and the PfEMP1 variant expressed, we used specific antibody panning to generate three sublines of the P. falciparum clone IT4, which expresses the PfEMP1 variants IT4VAR04, IT4VAR32b, and IT4VAR60. The knob density in each subline was then determined by atomic force microscopy (AFM) and scanning electron microscopy (SEM) and compared to PfEMP1 and knob-associated histidine-rich protein (KAHRP) expression. Selection for uniform expression of IT4VAR04 produced little change in knob density, compared to unselected IEs. In contrast, selection for IT4VAR32b expression increased knob density approximately 3-fold, whereas IEs selected for IT4VAR60 expression were essentially knobless. When IT4VAR60+ IEs were subsequently selected to express IT4VAR04 or IT4VAR32b, they again displayed low and high knob densities, respectively. All sublines expressed KAHRP regardless of the PfEMP1 expressed. Our study documents for the first time that knob density is related to the PfEMP1 variant expressed. This may reflect topological requirements to ensure optimal adhesive properties of the IEs. - IMPORTANCE Infections with Plasmodium falciparum malaria parasites are still responsible for many deaths, especially among children and pregnant women. New interventions are needed to reduce severe illness and deaths caused by this malaria parasite. Thus, a better understanding of the mechanisms behind the pathogenesis is essential. A main reason why Plasmodium falciparum malaria is more severe than disease caused by other malaria species is its ability to express variant antigens on the infected erythrocyte surface. These antigens are presented on membrane protrusions known as knobs. This study set out to investigate the interplay between different variant antigens on the surface of P. falciparum-infected erythrocytes and the density of the knobs on which the antigens are expressed. Such a direct analysis of this relationship has not been reported before but adds to the important understanding of the complexity of malaria antigen presentation.
Gesehen am 23.06.2020